A Survey on Block chain Technology beyond Bitcoin - Paul, Soumen; Ghosh, Ramkrishna (The journal of contemporary issues in business and government, 2021)
A Blockchain (BC) is essentially a distributed database of records or public ledger of all transactions or digital events that have been executed and shared among participating parties. Each transaction in the public ledger is verified by consensus of a majority of the participants in the system. And, once entered, information can never be erased. The BC contains a certain and verifiable record of every single transaction ever made. Bitcoin, the decentralized peer to peer digital currency, is the most popular example that uses BC technology. The digital currency bitcoin itself is highly controversial but the underlying BC technology has worked flawlessly and found wide range of applications in both financial and nonfinancial world. The main hypothesis is that the BC establishes a system of creating a distributed consensus in the digital online world. This allows participating entities to know for certain that a digital event happened by creating an irrefutable record in a public ledger. It opens the door for developing a democratic open and scalable digital economy from a centralized one. There are tremendous opportunities in this disruptive technology and revolution in this space has just begun. This white paper describes BC technology and some compelling specific applications in both financial and nonfinancial sector. We then look at the challenges ahead and business opportunities in this fundamental technology that is all set to revolutionize our digital world.